Design and Implementation of a Modular Biomimetic Infochemical Communication System. (20th July 2012) - Rácz, Z.; Cole, M.; Gardner, J.W.; Chowdhury, M.F.; Bula, W.P.; Gardeniers, J.G.E.; Karout, S.; Capurro, A.; Pearce, T.C.; Csurgay, Árpád I.; Porod, Wolfgang
SUMMARY We describe here the design and implementation of a novel biomimetic infochemical communication system that employs airborne molecules alone to communicate over space and time. The system involves the design and fabrication of a microsystem capable of producing and releasing a precise mix of biosynthetic compounds and a sensor system capable of detecting and decoding the ratiometrically encoded chemical information. The research inspired by biology has been based upon the biosynthetic pathways of infochemical production and information processing within the insect world. In this novel approach, the functional equivalents of the nanoscale biological machinery are implemented by combining the latest advances and convergence of expertise in the fields of biochemistry, molecular biology, neuroscience, micro‐ and nanofabrication, materials science, and smart sensor and microcircuit design. The biomimetic system comprises a micromachined bio‐reactor mimicking the sex gland of the female insect that releases a blend of pheromones in precisely controlled ratios, together with a cell‐based biosensor system, mimicking the antennae of the male insect. The signals from the biosensors are classified and ratios decoded using a field‐programmable gate array implementation of a neuromorphic model of the antenna lobe of the insect. We believe that this novel, smart infochemical communication system, inspired by the insect's behavior, could eventually be implemented in VLSI technology at low cost and low power with possible application in the fields of automatic identification and data capturing, product labeling, search and rescue, environmental monitoring, and pest control. Copyright © 2012 John Wiley & Sons, Ltd.